Increasing incidence and prevalence of metabolic syndrome in people living with HIV during the COVID-19 pandemic - Papaioannu Borjesson, Rebecka; Galli, Laura; Muccini, Camilla; Poli, Andrea; Clemente, Tommaso; Bottanelli, Martina; Gianotti, Nicola; Nozza, Silvia; Castagna, Antonella; Spagnuolo, Vincenzo (Frontiers in Medicine, 2023)
Introduction The aim of this study was to analyze the impact of COVID-19 pandemic restrictions on the prevalence and incidence of metabolic syndrome (MS), and to identify predictors of new MS cases in people living with HIV (PLWH). Methods This cohort study included PLWH followed at the IRCCS San Raffaele, Milan, Italy, with at least one body mass index (BMI) determination during the pre-pandemic period (1 December 2018 to 29 February 2020) and the pandemic period (1 March 2020 to 31 May 2021). MS diagnosis was based on NCEP ATP III 2005 criteria. Univariable Poisson regression model was used to compare MS incidence rates. Univariable mixed linear models estimated the crude mean change in metabolic parameters during each time period. Multivariable Cox proportional hazards model was used to assess risk factors for MS. Results This study included 1,564 PLWH, of whom 460 and 1,104 were with and without a diagnosis of MS, respectively, at the beginning of the pre-pandemic period, with an overall prevalence of MS of 29.4%. During the pre-pandemic period, 528/1,564 PLWH had MS, with a prevalence of 33.8% (95%CI = 31.5%–36.1%), while during the pandemic period, the number of PLWH with a diagnosis of MS increased to 628/1,564, with a prevalence of 40.2% (95%CI 37.8%–42.6%; McNemar’s test: p < 0.0001). Similarly, the MS incidence rate increased from 13.7/100 person-years of follow-up (PYFU; 95%CI = 11.7–16.0) in the pre-pandemic period to 18.5/100 PYFU (95%CI = 16.2–21.1) in the pandemic period (p = 0.004), with 201 subjects developing MS during the pandemic period. In addition, we observed a significant increase in the crude mean change during the pandemic period compared with the pre-pandemic period for: total cholesterol, LDL cholesterol, plasma glucose, blood pressure, and atherosclerotic cardiovascular disease (ASCVD) risk score. Finally, after adjustment for HIV risk factors, HBV, HCV, ART duration, duration of virologic suppression and use of INSTIs, age [adjusted hazard ratio (AHR) per 3 years older = 1.12 (95%CI = 1.08–1.17)], sex [AHR female vs. male = 0.62 (95%CI = 0.44–0.87)] and CD4+ cell count [AHR per 100 cells/μL higher = 1.05 (95%CI = 1.01–1.09)] were associated with the risk of MS. Conclusion The COVID-19 pandemic affected the metabolic profile of PLWH and increased the prevalence and incidence of MS.